2023
DOI: 10.3390/f14020243
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Pollen Morphology, Pollen Vitality and Preservation Methods of Gleditsia sinensis Lam. (Fabaceae)

Abstract: Gleditsia sinensis Lam. (Fabaceae) is an endemic species in China, which has a wide range of ecological functions and high economic value. G. sinensis belongs to androdioecy, and the stamens of perfect flowers are aborted, meaning that a perfect flower is a functional female flower. Understanding the dynamic process of flowering and the characteristics of pollen morphology effectively determine the viability of pollen vitality, and the suitable conditions for short-term storage of pollen can provide theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 68 publications
(87 reference statements)
1
6
0
Order By: Relevance
“…Microscopic examination of G. triacanthos L. pollen revealed oblate-spheroidal grains with tricolporate properties, elongated endoapertures at the equatorial regions, and a sporoderm surface displaying a reticulate pattern. These findings align with its assigned taxonomic classification, as the pollen of most caesalpinioid species follows a consistent pattern of being isopolar and tricolporate, with surface ornamentation that is either perforate or reticulate (Liu et al, 2023). Imaging of pollen surfaces unveiled the presence of pores and spinules in different J. regia L. types, with a notable variation in their distribution, making the findings intriguing.…”
Section: Discussionsupporting
confidence: 73%
“…Microscopic examination of G. triacanthos L. pollen revealed oblate-spheroidal grains with tricolporate properties, elongated endoapertures at the equatorial regions, and a sporoderm surface displaying a reticulate pattern. These findings align with its assigned taxonomic classification, as the pollen of most caesalpinioid species follows a consistent pattern of being isopolar and tricolporate, with surface ornamentation that is either perforate or reticulate (Liu et al, 2023). Imaging of pollen surfaces unveiled the presence of pores and spinules in different J. regia L. types, with a notable variation in their distribution, making the findings intriguing.…”
Section: Discussionsupporting
confidence: 73%
“…G. fera has been subjected to selection and there is a fast-growing cultivar available. Grafting onto G. fera as a rootstock increases the accumulation of photosynthetic products in the grafted plants ( Xiao, Zhao, Wang, & Jian, 2023b ). For growers whose harvest target is pod production, G. fera could be a good planting choice due to its fast growth, high seed yield, and full seeds.…”
Section: Discussionmentioning
confidence: 99%
“…G. sinensis (Fam. : Leguminosae ; Gen.: Gleditsia ) is a deciduous tree or shrub-like plant that is resistant to drought, cold, and pollution; has strong stress resistance; and is one of the first tree species used when returning farmland to forest ( Liu, Wang, Zhao, & He, 2022 ; Liu, Yang, Wang, & Zhao, 2023 ). The pod of G. japonica and G. delavayi are flat and irregularly twisted; In terms of cultivation and utilization, G. sinensis and G. delavayi are primarily grown and utilized in the southern regions of China, while G. sinensis and G. japonica are predominant in the northern regions.…”
Section: Introductionmentioning
confidence: 99%
“…However, diverse studies have revealed that pollen traits, particularly pollen size, may vary, depending on environmental conditions (Aguilar-García et al, 2012). In angiosperms, significant trends at higher taxonomic levels revolve around the quantity, placement, and composition of pollen apertures, the structure and layering of exine, and occasionally, considerations of size and sculpturing (Liu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%